2019
DOI: 10.1523/jneurosci.2059-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Tensin Promotes Axon Regeneration by Linking the Met-like SVH-2 and Integrin Signaling Pathways

Abstract: Axon regeneration is a conserved mechanism induced by axon injury that initiates a neuronal response leading to regrowth of the axon. In Caenorhabditis elegans, the initiation of axon regeneration is regulated by the JNK MAP kinase (MAPK) pathway. We have previously identified a number of genes affecting the JNK pathway using an RNAi-based screen. Analysis of these genes, called the svh genes, has shed new light on the regulation of axon regeneration, revealing the involvement of a signaling cascade consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…We sought to determine whether integrin functions upstream of the RHO-1 pathway in axon regeneration. We have previously reported that PAT-3/integrin β is involved in axonal regeneration ( Hisamoto et al, 2019 ). Here, we first confirmed the pat-3 mutant phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to determine whether integrin functions upstream of the RHO-1 pathway in axon regeneration. We have previously reported that PAT-3/integrin β is involved in axonal regeneration ( Hisamoto et al, 2019 ). Here, we first confirmed the pat-3 mutant phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…In the mammalian nervous system, integrins are involved in axon growth, synaptogenesis, and axon regeneration ( Nikonenko et al, 2003 ; Eva and Fawcett, 2014 ). The C. elegans integrins INA-1/integrin α and PAT-3/integrin β also participate in axon regeneration ( Pastuhov et al, 2016 ; Hisamoto et al, 2019 ). In this study, we investigated the relationship between integrin signaling and RhoA activation in the regulation of axon regeneration in C. elegans .…”
Section: Introductionmentioning
confidence: 99%
“…MAPK/ERK and PI3K/Akt signaling pathways can regulate protuberant 15 15 15 15 14 14 13 12 13 12 13 12 11 11 9 8 6 2 growth and protein synthesis related to neural plasticity, and it can assist in the normal development of nerve cells, which may protect against SCZ [22]. e initiation of nerve axon regeneration is regulated by the MAPK pathway and this initiates a neuronal response [23]. Further studies should explore directly whether the CDMGs in the present study are associated with SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction from worms and immunoprecipitation were carried out as described previously (Hisamoto et al 2019). For PNGase treatment, the bead pellets were further washed with wash buffer (20 mM Tris-HCl, pH 7.5, 50 mM NaCl, 5 mM EDTA) for several times and then treated with Rapid PNGase F (New England Biolabs) according to the instruction manual.…”
Section: Methodsmentioning
confidence: 99%